Metagenomic Insight Into Patterns and Mechanism of Nitrogen Cycle During Biocrust Succession - Wang, Qiong; Han, Yingchun; Lan, Shubin; Hu, Chunxiang (Frontiers in Microbiology, 2021)
The successional ecology of nitrogen cycling in biocrusts and the linkages to ecosystem processes remains unclear. To explore this, four successional stages of natural biocrust with five batches of repeated sampling and three developmental stages of simulated biocrust were studied using relative and absolute quantified multi-omics methods. A consistent pattern across all biocrust was found where ammonium assimilation, mineralization, dissimilatory nitrite to ammonium (DNiRA), and assimilatory nitrate to ammonium were abundant, while denitrification medium, N-fixation, and ammonia oxidation were low. Mathematic analysis showed that the nitrogen cycle in natural biocrust was driven by dissolved organic N and NO3-. pH and SO42- were the strongest variables affecting denitrification, while C:(N:P) was the strongest variable affecting N-fixation, DNiRA, nitrite oxidation, and dissimilatory nitrate to nitrite. Furthermore, N-fixation and DNiRA were closely related to elemental stoichiometry and redox balance, while assimilatory nitrite to ammonium (ANiRA) and mineralization were related to hydrological cycles. Together with the absolute quantification and network models, our results suggest that responsive ANiRA and mineralization decreased during biocrust succession; whereas central respiratory DNiRA, the final step of denitrification, and the complexity and interaction of the whole nitrogen cycle network increased. Therefore, our study stresses the changing environmental functions in the biocrust N-cycle, which are succession-dependent.